2017
DOI: 10.3390/app7060606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nozzle Configuration on Rock Erosion Under a Supercritical Carbon Dioxide Jet at Various Pressures and Temperatures

Abstract: Abstract:The supercritical carbon dioxide (SC-CO 2 ) jet offers many advantages over water jets in the field of oil and gas exploration and development. To take better advantage of the SC-CO 2 jet, effects of nozzle configuration on rock erosion characteristics were experimentally investigated with respect to the erosion volume. A convergent nozzle and two Laval nozzles, as well as artificial cores were employed in the experiments. It was found that the Laval nozzle can enhance rock erosion ability, which larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Since many types of abrasion become concrete damage problem, there are many abrasion test methods. Some researchers [9][10][11][12][13] use current commonly used test methods to determine frictional attrition under specific conditions, including the case of limiting amount of tiny grains on a small surface area of concrete. In general, the abrasion resistance is determined by the interface properties between the paste and aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Since many types of abrasion become concrete damage problem, there are many abrasion test methods. Some researchers [9][10][11][12][13] use current commonly used test methods to determine frictional attrition under specific conditions, including the case of limiting amount of tiny grains on a small surface area of concrete. In general, the abrasion resistance is determined by the interface properties between the paste and aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure data when the SCO2 flow upstream the organ-pipe nozzle was most stable were used for the statistical analysis of the impact pressure characteristics of SEOSJs. More details of the experimental circuit are given in our prior studies [6,15]. The schematic diagram of the organ-pipe nozzle used in the experiments is shown in Figure 3.…”
Section: Experimental Setup 21 Experiments Apparatus and Proceduresmentioning
confidence: 99%
“…When the jets were ejected from the nozzle, cavitation cloud developed completely after a certain distance, then broke and collapsed which indicated that cavitation need enough distance to develop. If the distance between the target and the nozzle outlet was within the effective range-that is, it was within the length range of the cavitation cloud and developed completely-the cavitation bubbles hit the wall surface, broke into small bubbles, and formed a micro-jet near the wall surface with huge local energy, which acted on the surface of the target to form effective damage [32,33]. Moreover, if the standoff distance was not enough for bubble development, the effect of the jets on the target was also affected.…”
Section: Influence Of Cavity Lengthmentioning
confidence: 99%